Strategi Pengusaha Jawa Timur Dalam Meningkatkan Produktivitas Industri Melalui Pengembangan Sumber Daya Manusia - Firdausii Khoirunnisa; Maharani Ikaningtyas (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2024)
This research explores the strategies implemented by entrepreneurs in East Java to enhance industrial productivity through human resources development (HRD). Within the dynamic economic context and diverse industrial structure, this study aims to identify and analyze innovative strategies used by entrepreneurs to address challenges related to the quality and quantity of competent human resources. The research methodology employed a qualitative approach with document analysis and secondary data from various relevant sources. Findings highlight the importance of collaboration among industrial sectors, government, and educational institutions in improving HRD quality, alongside enhancing effective implementation of Occupational Health and Safety (OHS) policies in workplaces. The implications of this research suggest adopting HRD-focused strategies and improving OHS practices to enhance industrial competitiveness in East Java and support sustainable economic growth.